Addressing COVID-19 vaccine hesitancy in South Africa- moving beyond a reliance on information-based responses - Sara Cooper; Heidi van Rooyen; Charles S. Wiysonge (Taylor & Francis Group, 2022)
It has been over a year since South Africa officially began its national COVID-19 vaccination programme. Yet, currently only half of the adult population is fully vaccinated. While supply-related challenges continue to contribute to suboptimal vaccination coverage, so too does vaccine hesitancy. Drawing on research conducted over the last year, we highlight some overarching insights around the nature and drivers of COVID-19 vaccine hesitancy in South Africa and how this complex phenomenon might be addressed. We have found multiple socio-economic and political root causes of COVID-19 vaccine hesitancy, many of which are not knowledge-related. These include inter alia fear and uncertainty, practical challenges around access, experiences of poverty and marginalization, and the ongoing geopolitics surrounding the pandemic. Intervention strategies therefore need to form part of broader development and trust-building measures that focus on relationships, transparency, inclusion, equity and justice. This is essential if we hope to bolster acceptance of and demand for vaccines during and beyond the COVID-19 pandemic.